AT AMINDA SKIN CARE'S MAKASSAR BRANCH, THE IMPACT OF CUSTOMER EXPERIENCE, BRAND AWARENESS, AND CUSTOMER SATISFACTION ON CUSTOMER LOYALTY - Muhammad Islah Idrus; Syamsu Rijal; Muh. Ihsan Said Ahmad (Transformasi: Journal of Economics and Business Management, 2023)
The aim of this study was to evaluate brand awareness, customer happiness, and customer experience in relation to consumer loyalty to Aminda Skin Care at the Makassar Branch. The population of the study consists of Aminda Skin Care customers. The sample for the study consisted of 96 individuals, and information was gathered using a questionnaire. The data are analysed using SPSS 20 after the hypothesis is tested using multiple linear regression analysis. The results of this study indicate that customer experience has little impact on loyalty. Brand recognition and customer satisfaction have a significant impact on consumer loyalty.